Single spore culture of Arbsucular Mycorrhizal Fungi from the Rhizosphere of Siompu Citrus (Citrus nobilis Lour.) - Husna, Husna; H, Rahmawati; Tuheteru, Faisal Danu; Arif, Asrianti; Nurdin, Wiwin Rahmawati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Arbuscular mycorrhizal fungi (AMF) are the most common type of mycorrhiza and are the result of an obligate symbiont between fungi and roots that form a mutualistic symbiosis in several plants. This research aims to determine the increase in AMF spore production from the rhizosphere of Siompu oranges using single culture at the Nggula-nggula location. This research was conducted at the Plastic House of the Indonesian Mycorrhizal Association (AMI) Southeast Sulawesi Branch, UHO Old Campus and the UHO Forestry and Environmental Science Laboratory Unit which lasted for 3 months from May – July 2023. This research was designed using a Completely Randomized Design consisting of 12 treatments, each treatment was repeated 3 times and 5 plants were used for each repetition so that the total plants were 180 plants. The results showed that AMF spore production was not influenced by the type of AMF treatment. The types of spores produced in a single spore culture range from 13-127 spores at 3 months of age.